Karakteristik Produksi Kambing Peranakan Etawa Dan Kambing Kacang Pada Sistem Pemeliharaan Berbeda Di Kecamatan Toari, Kabupaten Kolaka - Nafiu, L. O.; Pagala, M. A.; Mogiye, S. L. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2020)
Toari sub-district has a population of 4,434 head or 18.47% of the total 24,003 head of the goat population in Kolaka Regency. The purpose of this study was to determine the characteristics of Etawa crossbreed goats and bean goats in different maintenance systems in the Toari District. The population in this study were all breeders of Etawa Peranakan goats and peanut goats in the Toari District with the research sample of Ranomentaa, Rano Jaya, Lakito, and Toari villages. The sampling method was determined by purposive sampling, ie the sample was determined intentionally while the data used were primary and secondary data. Primary data were obtained through interviews of 100 respondents while secondary data were obtained from the District, village, and related government offices. The results showed that the production of Etawa Peranakan goat and PE Goat Production characteristics (body weight, birth type, chest circumference, body length, shoulder height, and pelvic height) General Etawa (PE) goats were higher compared to pea goats both in maintenance intensive, semi-intensive or extensive system.